Association of Ischemic Core Imaging Biomarkers With Post-Thrombectomy Clinical Outcomes in the MR CLEAN Registry - Koopman, Miou S.; Hoving, Jan W.; Kappelhof, Manon; Berkhemer, Olvert A.; Beenen, Ludo F. M.; van Zwam, Wim H.; de Jong, Hugo W. A. M.; Dankbaar, Jan Willem; Dippel, Diederik W. J.; Coutinho, Jonathan M.; Marquering, Henk A.; Emmer, Bart J.; et al. (Frontiers in Neurology, 2022)
Background: A considerable proportion of acute ischemic stroke patients treated with endovascular thrombectomy (EVT) are dead or severely disabled at 3 months despite successful reperfusion. Ischemic core imaging biomarkers may help to identify patients who are more likely to have a poor outcome after endovascular thrombectomy (EVT) despite successful reperfusion. We studied the association of CT perfusion-(CTP), CT angiography-(CTA), and noncontrast CT-(NCCT) based imaging markers with poor outcome in patients who underwent EVT in daily clinical practice. Methods: We included consecutive EVT-treated patients (2016–2017) with an anterior circulation occlusion from the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) Registry with available baseline CTP,CTA, and NCCT. We used multivariable binary and ordinal logistic regression to analyze the association of CTP ischemic core volume, CTA-Collateral Score (CTA-CS) and Alberta Stroke Program Early CT Score (ASPECTS) with poor outcome (modified Rankin Scale score (mRS)5-6) and likelihood of having a lower score on the mRS at 90 days. Results: In 201 patients, median core volume was 13(IQR 5-41)mL. Median ASPECTS was 9(IQR 8-10). Most patients had grade 2 (83/201;42%) or grade 3 (28/201;14%) collaterals. CTP ischemic core volume was associated with poor outcome (aOR per 10 mL 1.02[95%CI 1.01-1.04]) and lower likelihood of having a lower score on the mRS at 90 days (aOR per 10 mL 0.85[95% CI 0.78-0.93]). In multivariable analysis, neither CTA-CS nor ASPECTS were significantly associated with poor outcome or the likelihood of having a lower mRS. Conclusions: In our population of patients treated with EVT in daily clinical practice, CTP ischemic core volume is associated with poor outcome and lower likelihood of shift towards better outcome in contrast to either CTA-CS or ASPECTS.